1989
DOI: 10.1136/jech.43.2.107
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish two county trial of mammographic screening for breast cancer: recent results and calculation of benefit.

Abstract: The Swedish two county trial of breast cancer screening is now in its tenth year. This paper presents detailed results on mortality from breast cancer and from all other causes, and on the population denominators at risk for each of the first 8 years of follow up, for each county separately. These data represent a two year update on the last major report. Results show an increasingly significant deficit in deaths from breast cancer among the 77 092 women invited to screening relative to the 56 000 not invited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
0
11

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(130 citation statements)
references
References 11 publications
2
117
0
11
Order By: Relevance
“…2,3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results. 21,22 In a single report of race-specific survival rates, Shapiro et al showed that substantially more white than black women in the control group survived breast cancer five years from diagnosis (60.9 % versus 47.1 %).…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…2,3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results. 21,22 In a single report of race-specific survival rates, Shapiro et al showed that substantially more white than black women in the control group survived breast cancer five years from diagnosis (60.9 % versus 47.1 %).…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…
The reduced breast cancer mortality found in several major studies (Shapiro et al, 1982;Collette et al, 1984;Verbeek et al, 1984;Tabar et al, 1985Tabar et al, , 1989Palli et al, 1986) is the rationale for screening with mammography. In order to justify the continued use of a screening procedure, subjects correctly classified as positive at screening should receive a benefit.
…”
mentioning
confidence: 99%
“…However, even in the New York trial and the Two Counties trial the validity of reviewers conclusions are not immune from a bias which could favour screening. Both studies (Shapiro et al, 1988;Tabar et al, 1989) (Chamberlain, 1982). The purpose of making populationbased mortality comparisons rather than case-fatality comparisons is the avoidance of lead time bias and length-biased sampling effects but, if stage is taken into consideration in judging between competing causes of death, review of the cause of death is unhelpful.…”
Section: Discussionmentioning
confidence: 99%
“…The records of 99% of the women were successfully flagged at the NHS Central Registries and it is these women, aged 45 to 72, whose mortality has been analysed. For (Tabar et al, 1985;Tabar et al, 1989) (Table II). If, however, in those cases where the assessors were uncertain because records were scanty, the certifying doctors were given the benefit of the doubt, the number of cases of disagreement between assessor and death certificate would have been reduced from 56 (6.0%), as shown in Table II, to 12 (1.3%).…”
Section: Methods Of Reviewmentioning
confidence: 99%